Pengembangan Sistem Pengelolaan Keuangan Kepegawaian Universitas Atma Jaya Makassar - Ridnaldy Yunior Carolus (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2019)
The main goal of this thesis is to develop formerly made into one systems and integrating with a financial system UAJM to be a system that can support the process financial management and employment can help improve performance in personalia to managing personnel at the University of Atma Jaya Makassar.